Impactos del reconocimiento multicultural en el archipiélago de San Andrés, Providencia y Santa Catalina: entre la etnización y el conflicto social (2011)
By defining itself as a multiethnic and multicultural nation in 1991, Colombia recognized special rights and statutes to a diversity of populations and their territories. Among them, the native population of the Archipelago of San Andrés, Providencia, and Santa Catalina achieved recognition under the new Constitution. This article aims to present some of the implications of this multicultural recognition focusing particularly on the process of ethnicization of the native population of the Archipelago and the emergence of different conflicts among the native population and the Colombian State, as well as those among the native population and migrants from Colombia's mainland. These conflicts reveal the clash between two identities on the islands: on the one hand, the diasporic one, which is a consequence of the Caribbean's characteristic processes of migration and exchange, and on the other hand, ethnic enclosure as a result of multicultural ethnic recognition.